Ferroptosis-related gene signatures in neuroblastoma associated with prognosis - Chen, Yiru; Li, Zihao; Cao, Qingtai; Guan, Haoyu; Mao, Longfei; Zhao, Mingyi (Frontiers in Cell and Developmental Biology, 2022)
Background: Ferroptosis, a form of regulatory cell death, has been found to be involved in the development of various tumors. Peripheral neuroblastoma (NB) is one of the most common extracranial solid tumors in children, it has been reported that it may become a possible treatment of NB by regulating the ferroptosis of tumor cells in the future. However, it remains unclear how ferroptosis contributes to the development of neuroblastoma. Methods: Expression data was obtained from two independent cohorts (GEO and Arrayexpress database). Univariate Cox, multivariate Cox analysis, the least absolute shrinkage and selection operator (Lasso) algorithm were applied to build a prognostic signature, whose performance was evaluated by the area under the receiver operating characteristic curve (AUC) and Kaplan–Meier curves. Drug sensitivity analysis were performed by collecting data from Cell Miner™. Results: The FRG prognostic signature contains 8 genes: PROM2, AURKA, STEAP3, CD44, ULK2, MAP1LC3A, ATP6V1G2 and STAT3, and all of them except AURKA were highly expressed in stage 1 neuroblastoma. And the high risk group which was stratified by the signature was associated with a shorter overall survival than tow risk group. More ferroptosis-related biological processes are enriched in high-risk groups, which was showed in GSEAs. Conclusions: Ferroptosis-related genes are differentially expressed between stage 1 and stage 4 NB. The FRG signature successfully stratified NB patients into two risk groups and it is able to accurately predict overall survival in neuroblastoma.